Ruminal Biohydrogenation Pattern of Poly-Unsaturated Fatty Acid as Influenced by Dietary Tannin - Anuraga Jayanegara (Indonesian Center for Animal Research and Development, 2013)
Abstract Large amounts of polyunsaturated fatty acids undergo transformation processes in the rumen through microbial biohydrogenation to form fatty acids with higher saturation degree. The respective process explains the high content of saturated fatty acids in products of ruminants and the potential risk of consumers’ health by consuming such products. Various nutritional approaches have been attempted to modulate biohydrogenation process in order to obtain healthier fatty acid profile from consumers’ perspective. The present paper is aimed to review the influence of dietary tannin, a naturally produced plant secondary compound, on the pattern of polyunsaturated fatty acids biohydrogenation occurring in the rumen. The effect of tannin on some key fatty acids involved in biohydrogenation process is presented together with the underlying mechanisms, particularly from up-to-date research results. Accordingly, different form of tannin as well as different level of the application are also discussed. Key words: Tannin, biohydrogenation, fatty acid, ruminant